Hairy and enhancer of split 6 prevents hepatic lipid accumulation through inhibition of Pparg2 expression. Issue 10 (8th November 2017) - Park, Jung Eun; Lee, Mikang; Kim, Seong‐Chul; Zhang, Yanqiao; Hardwick, James P.; Lee, Yoon Kwang
Abstract : Peroxisome proliferator‐activated receptor gamma (PPARγ) is a master regulator for white adipocyte differentiation and lipid storage. The increased level of hepatic PPARγ2 isoform reprograms liver for lipid storage and causes abnormal fat accumulation in certain pathophysiologic conditions. The current study aimed to investigate a role of transcriptional repressor hairy and enhancer of split 6 (HES6) in the regulation of Pparg2 expression and hepatic steatosis induced by diet. Liver‐specific overexpression of Hes6 using adenovirus reduced Pparg2 messenger RNA levels by 90% and hepatic triglyceride accumulation by 22% compared to the levels in mice injected with an adenoviral empty vector with Western diet feeding. In sharp contrast, silencing Hes6 gene expression using short hairpin RNA increased hepatic lipid accumulation and Pparg2 messenger RNA levels by 70% and 4‐fold, respectively. To locate hepatocyte nuclear factor 4 alpha (HNF4α) binding site(s), through which repressional activity of HES6 is mediated, a 2.5‐kb Pparg2 promoter‐driven luciferase reporter was constructed for transient transfection assays. Subsequently, chromatin immunoprecipitation and electrophoretic mobility shift assays were performed. An HNF4α binding consensus sequence was identified at 903 base pairs upstream from the transcription start site of Pparg2 . Deletion or point mutation of the sequence in a luciferase reporter containing the Pparg2 promoter abolished HNF4α‐mediated activation in HeLa cells. Chromatin immunoprecipitation and electrophoretic mobility shift assays further confirmed direct recruitment and binding of HNF4α to the site. Gene expression analysis with liver samples from subjects with nonalcoholic steatohepatitis suggested that the axis of the Hes6–Hnf4a–Pparg2 transcriptional cascade is also responsible for hepatic fat accumulation in humans. Conclusion : HES6 represses Pparg2 gene expression, thereby preventing hepatic lipid accumulation induced by chronic Western diet feeding or pathophysiologic conditions. ( Hepatology Communications 2017;1:1085–1098)